Determination of Lead and Cadmium in Marine Water and Crabs (Pachygrapsus marmoratus) from Tolmeitha Coast, Libya - Ahmad Balal; Mohamed Obid; Hanibal Khatab; Hamad Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
In this study, the concentrations of Lead and Cadmium metals were determined in water and Crab (Pachygrapsus marmoratus) samples collected from some locations around Tolmaitha city coast (Eastern North) of Libya. The samples were collected during two different seasons (Winter and Summer). The atomic absorption method was used to estimate the studied heavy metals. The results of this study recorded that the concentrations of Lead ranged between (0.3 – 52.15 ppm), and for the Cadmium contents ranged between (0.05-0.084 ppm). High concentrations were recorded for the lead in Crab samples (1.25 -169.7 ppm) and the cadmium concentrations (0.16 -4.32 ppm). The results of this indicated for presence of small variations of the selected metals in the organs and shields of the studied crabs. But in general, High concentrations were recorded in the carapace, more than the permissible limit of WHO values.